2000
DOI: 10.1046/j.1469-8137.2000.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Tansley Review No. 116

Abstract: Summary 449 I. INTRODUCTION 450 II. THE PARTNERS 451 1. Cyanobionts and their role 451 2. Hosts and their role 453 3. Location of cyanobionts in their hosts 455 III. INITIATION AND DEVELOPMENT OF SYMBIOSES 458 1. Initiation of symbioses 458 2. Geosiphon pyriforme 458 3. Cyanolichens 459 4. Liverworts and hornworts 460 5. Azolla 460 6. Cycads 461 7. Gunnera 461 IV. THE SYMBIOSES 462 1. Geographical distribution and ecological significance 462 2. Benefits to the partners 462 (a) Benefits to the cyanobionts 462 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 308 publications
(56 citation statements)
references
References 292 publications
(316 reference statements)
2
49
0
Order By: Relevance
“…Overall, DDN released from internal symbionts should be easier and faster accessible to the coral host as compared to DDN released from external symbionts. This has been previously shown for terrestrial plant-diazotroph symbioses in which DDN release by diazotrophs and uptake by the host occurs at interfaces where both partner are in close contact to each other (Rai et al, 2000). conditions.…”
Section: Mechanisms Of Ddn Uptake and Transfer Among Compartments Of supporting
confidence: 64%
See 1 more Smart Citation
“…Overall, DDN released from internal symbionts should be easier and faster accessible to the coral host as compared to DDN released from external symbionts. This has been previously shown for terrestrial plant-diazotroph symbioses in which DDN release by diazotrophs and uptake by the host occurs at interfaces where both partner are in close contact to each other (Rai et al, 2000). conditions.…”
Section: Mechanisms Of Ddn Uptake and Transfer Among Compartments Of supporting
confidence: 64%
“…However, the exact mechanisms of release and uptake remain unexplored also for plant-diazotroph symbioses, but many of the interface membranes of both partners possess H + -ATPase, implying the presence of transport systems (Rai et al, 2000). Using multi-isotope imaging mass spectrometry Lechene et al (2007) imaged and measured N 2 fixation by endosymbiotic diazotrophs associated with shipworms.…”
Section: Mechanisms Of Ddn Uptake and Transfer Among Compartments Of mentioning
confidence: 99%
“…It has been shown that nitrogen deprivation stimulates modern symbiotic associations [86,90] and that nitrogenrich conditions on the contrary facilitate the dissipation of pre-established symbiotic relationships [86]. If nitrogen was the key factor for the host and symbiont to form the initial association, it is congruent with the finding that present-day members of filamentous, heterocyst-forming and N 2 -fixing cyanobacterial sections IV and V have a collection of genes most similar to that possessed by the plastid ancestor [39,46].…”
Section: Plastid Origin and The Origin Of Oxygenic Photosynthesismentioning
confidence: 99%
“…In nature, highly diverse taxonomic hosts form symbiotic or endosymbiotic associations with photosynthesizing and N 2 -fixing cyanobacteria in various environments. They range from autotrophic algae and plants [86] to heterotrophic fungi where over 1500 species represent cases of lichen symbioses with cyanobacteria [87]. Specifically in plants, cyanobacterial symbioses are present in the four main groups -gymnosperms, angiosperms, pteridophytes and bryophytes [86].…”
Section: Why: the Physiological Context Of Plastid Originmentioning
confidence: 99%
See 1 more Smart Citation